Studying of antagonistic activity of some probiotics against bacteria P.mirabilis isolated from kidney stones - Amin S.Badawy; Akeel H. Al.Assie; Halah A. A. Al-Hadithi (Tikrit Journal of Pure Science, 2023)
This study Included  (68)gritkidneys samples collected from  patients undergoingsurgerylin hospitals in Tikrit city from  periodbetween  April 2012to  May2013.